1992
DOI: 10.1111/j.1099-0860.1992.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Empowerment in Child Protection Work

Abstract: SUMMARY. The authors argue in this paper that the dominance of legal and professional approaches that individualise and pathologise child abuse has left welfare workers ill‐equipped to respond to the emergent interest in parent's and children's rights. They suggest that such approaches fail to take adequate account of inequalities based on class, gender and race and the socially‐constructed aspects of adult‐child relationships. They develop a concept of empowerment, informed by radical traditions within welfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They suggest that it can serve to counteract some of the powerlessness children may feel from having been abused. Katz (1997, p. 165 (Boushel and Lebacq, 1992;Butler and Williamson, 1994). Research into children and young people's views indicates that most would prefer to have more involvement in decisions related to their own welfare and that being excluded may be experienced by them as being more harmful (Boylan and Wyllie, 1999;Butler and Williamson, 1994;Marshall, 1997;Shemmings, 1996).…”
Section: Policy and Research Contextmentioning
confidence: 96%
“…They suggest that it can serve to counteract some of the powerlessness children may feel from having been abused. Katz (1997, p. 165 (Boushel and Lebacq, 1992;Butler and Williamson, 1994). Research into children and young people's views indicates that most would prefer to have more involvement in decisions related to their own welfare and that being excluded may be experienced by them as being more harmful (Boylan and Wyllie, 1999;Butler and Williamson, 1994;Marshall, 1997;Shemmings, 1996).…”
Section: Policy and Research Contextmentioning
confidence: 96%
“…Lupton & Nixon () describe ‘partnership’ between professionals and service users as the process and ‘empowerment’ of the service user as the outcome. Whilst recognizing the argument that in child protection the statutory responsibilities of the social worker make it difficult to conceptualize how a family might be empowered, they take the view of Boushel and Lebacq () that empowering practice offers interventions that are less discriminatory and more strengths‐based by ‘supporting the positive factors of the lives of children and their carers’ (p. 49). Marsh & Crow () argue that partnership cannot be conceived as being about ‘equal power’ as this would be unrealistic in a child protection setting and they argue that partnership is about diversity ‘within a common frame of principles’ (p. 55).…”
Section: Fgcs: Reparation and Empowermentmentioning
confidence: 99%
“…It has also long been argued that scant attention is paid to the factors in society which serve to create poverty and stress for low-income families (Boushel & Lebacq, 1992;Bond, 2002;Buckely, 2005). In particular, although child maltreatment occurs across economic status, a number of authors have indicated that children from poor families are over-represented in child abuse case loads (Channer & Parton, 1990;Maluccio & Fein, 1985;Pecorra, Carlson, Reese & Bartholomew, 1992;Pelton, 1982;Roberts, 2000).…”
Section: Strengthening Children's Own Familiesmentioning
confidence: 99%